Manajemen peserta didik dalam meningkatkan daya saing pada mata pelajaran matematika di Mts darunnajah 2 cipining - Achmad Faqih; Taufik Nur Aziz; Nailil Muna Sholihah (PT. Banjarese Pacific Indonesia, 2025)
MTs Darunnajah 2 Cipining is a dormitory-based institution, often referred to as an Islamic boarding school, which fosters a greater sense of independence among its students compared to non-dormitory schools. This research aims to explore the strategies employed by students to enhance their competitiveness in mathematics at MTs Darunnajah 2 Cipining. The findings reveal the distinct characteristics that students exhibit when competing in their mathematics lessons at this institution.